Cambodia Confounds the Peacemakers, 1979-1998 - Brown, MacAlister; Zasloff, Joseph J. (Williams College Center for the Humanities and Social Sciences, 2019)
The peacemaking efforts in Cambodia since the dispersal of the Khmer Rouge in 1979 were the most comprehensive ever undertaken by the international community. Two seasoned observers of Southeast Asia now offer a detailed account of this endeavor, including the negotiation and planning that produced the United Nations Transitional Authority in Cambodia (UNTAC) and a free and fair election in 1993. MacAlister Brown and Joseph J. Zasloff unravel the tangled web of civil war from 1979 to the coup d'etat by Hun Sen in 1997, and the effort to hold a second election in summer 1998. They trace the years of diplomacy and warfare sustained by outside powers, the establishment of a constitutional government, and the achievements and shortfalls of the U.N. presence in Cambodia. With the results of the 1998 election appraised in an epilogue, this engaging book provides the most complete and up-to-date account of international peacekeeping and political rescue in long-suffering Cambodia.